Fabrication of conductive and superhydrophobic poly(lactic acid) nonwoven fabric for human motion detection. Issue 26 (22nd April 2022) - Zeng, Qingtao; Lai, Dehui; Ma, Piming; Lai, Xuejun; Zeng, Xingrong; Li, Hongqiang
Abstract: In recent years, piezoresistive pressure sensors with superhydrophobicity have aroused considerable attention. In addition, to comply with "sustainable development" strategy, the sensors fabricated with eco‐friendly materials is of great theoretical and practical significance. Herein, tannic acid (TA) was first absorbed on the surface of poly(lactic acid) (PLA) nonwoven fabric by simple dipping method. After that, silver (Ag) particles were in situ generated on the surface to construct roughness with the reduction role of TA by immersing the fabric into silver nitrate aqueous solution. Finally, n‐lauryl mercaptan was grafted on the Ag particles via Ag–S bonds to provide low surface energy, and a conductive and superhydrophobic PLA (CSPLA) nonwoven fabric was fabricated. The obtained CSPLA nonwoven fabric had a high water contact angle of 150.3°. The fabric‐based piezoresistive pressure sensor possessed high sensitivity, fast response, good stability, and excellent reusability, and was successfully applied for detecting various human motions including voice recognition, joint bending, stomping, walking, and jumping. The fabricated sensor has great application potential in the fields of touchable displays, electronic skins, intelligent robotics, and wearable devices. Abstract :